The Effectivity Google Display Network and Google Video Network in YouTube: A Literature Review - Rahmad Agus Dwianto; Nur Wening (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2021)
The purpose of this study is to analyze the effectiveness of the Google Display Network on YouTube. This study uses a literature review that describes the problems or successes that appear on the features on the Google Display Network platform. This literature review also explains ways to anticipate these problems, such as focusing on the marketing targets to be achieved. The findings in this study are that there are still many products that are not relevant to the main video that is used as a means of advertising of their products. Meanwhile, according to data from businessmen who place ads on YouTube, many successful businesses increase demand for their products and generate a lot of profit. Successful business people already know the marketing targets that their products will target and also know the main video criteria that will be used as a means of marketing of their products.